1999
DOI: 10.1126/science.284.5418.1368
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Polyketide Synthase Activity by Accessory Proteins During Lovastatin Biosynthesis

Abstract: Polyketides, the ubiquitous products of secondary metabolism in microorganisms, are made by a process resembling fatty acid biosynthesis that allows the suppression of reduction or dehydration reactions at specific biosynthetic steps, giving rise to a wide range of often medically useful products. The lovastatin biosynthesis cluster contains two type I polyketide synthase genes. Synthesis of the main nonaketide-derived skeleton was found to require the previously known iterative lovastatin nonaketide synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
576
1
24

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(622 citation statements)
references
References 24 publications
21
576
1
24
Order By: Relevance
“…tatin is synthesized via the polyketide pathway [18,19]. After addition of lactose at 144 h of culture, a lovastatin specific generation rate of 0.242 mg (g biomass) −1 h −1 was obtained for the three C:N values tested.…”
Section: Resultsmentioning
confidence: 99%
“…tatin is synthesized via the polyketide pathway [18,19]. After addition of lactose at 144 h of culture, a lovastatin specific generation rate of 0.242 mg (g biomass) −1 h −1 was obtained for the three C:N values tested.…”
Section: Resultsmentioning
confidence: 99%
“…In a noniterative modular PKS, each module is used only once, and the polyketide intermediate is transferred to a downstream module for chain elongation. The well-known anti-cholesterol natural product lovastatin is synthesized by two noniterative type I PKSs in Aspergillus terreus (2), whereas the antibiotic erythromycin is synthesized by a bacterial iterative type I PKS consisting of a loading module and six extension modules (3). Different from both of these is type II PKS, a large multienzyme complex of small, discrete enzymes with particular functions.…”
Section: Introductionmentioning
confidence: 99%
“…Selective processing during two successive iterations of polyketide chain extension is a known feature in highly reducing fully iterative polyketide synthases 29, 30, 31. In the LovB PKS, for example, which synthesizes the nonaketide core of the cholesterol‐lowering compound lovastatin using a single PKS module, an integral methyltransferase domain selectively methylates the β‐ketothioester formed after three rounds of chain extension 29.…”
mentioning
confidence: 99%
“…In the LovB PKS, for example, which synthesizes the nonaketide core of the cholesterol‐lowering compound lovastatin using a single PKS module, an integral methyltransferase domain selectively methylates the β‐ketothioester formed after three rounds of chain extension 29. In vitro analysis of model thioester substrates for LovB has demonstrated that the methyltransferase is exquisitely specific for the tetraketide substrate, and that for this substrate, methylation effectively outcompetes prior ketoreduction 32.…”
mentioning
confidence: 99%